Carotid ultrasound for cardiovascular risk prediction: From intima-media thickness to carotid plaques - Ravi R Kasliwal (Journal of the Indian Academy of Echocardiography & Cardiovascular Imaging, 2017)
Carotid intima-media thickness (CIMT) and nonstenotic carotid plaques are established measures of subclinical atherosclerosis and are useful for prediction of future cardiovascular disease (CVD) risk. Compared with CIMT, the incremental predictive value of carotid plaques is more robust. Although the guidelines differ, carotid ultrasound-based assessment of CIMT and carotid plaques has a role in risk stratification and management of asymptomatic individuals who present with one or more CVD risk factors. The presence of significantly elevated CIMT or carotid plaque burden should lead to reclassification of the individuals into high-risk category with the appropriate intensification of the risk reduction measures. In addition, demonstration of increased CIMT and/or presence of the plaques may also help in improving patients' health behavior and their compliance toward antiatherosclerotic measures. In future, plaque progression/regression assessment by three-dimensional ultrasound and the use of contrast agents may further enhance the utility of carotid ultrasound for monitoring the clinical course of atherosclerotic vascular disease.